La Interculturalidad en el desarrollo del pensamiento filosófico en niños de Preparatoria - Román Proaño, Zoila Grimaneza (2024)
ABSTRAC The purpose of this research is to describe the level of development of philosophical thinking in high school children of the educational units of the Riobamba canton from an intercultural approach, with the purpose of determining whether interculturality affects the development of philosophical thinking in high school children of the educational units of the Riobamba canton 2022-2023, through the qualitative and quantitative paradigm, for the revitalization of the intercultural project. Interviews and surveys were applied as techniques and as instruments, the questionnaires were applied to teachers and children from five educational establishments in the city of Riobamba. In the same way, a questionnaire was developed for the interviews applied to two experts in Philosophy, in the results it was possible to determine that interculturality is present in each of the high school children, which leads to the conclusion that the younger the children are integrated into the philosophy of interculturality, they will grow up free of prejudices, respecting and being empathetic when merits the situation, as I also believe that teachers should insert into their class hours philosophical aspects that can be discussed with the children, thus achieving the development of critical, reflective, ingenious, free, open thinking, that is, It must accompany children in the fight to mature and grow, through strategies such as stories, stories, games and art. Keywords: interculturality, philosophy